Pathologicoanatomic changes in calves at sepsis caused by rhodococci - A. A. Blokhin; O. A. Burova; E. A. Liskova (Аграрная наука Евро-Северо-Востока)
Results of clinical, pathologo-anatomic, histopathologic and bacteriologic studies at an experimental infection caused by an injection of 35.0 ml of suspension containing 1.0 million CFU/ml show that rhodococci are involved in the initiation and development of septic processes in calves. It was estimated that the pathologianatomic pattern of sepsis caused by rhodococci is characterized by impaired homeostasis occurring as DVC-syndrome, sludge-phenomenon, hemorrhages in the mucous and serous membranes, systemic vasculitis with fibrinoid necrosis of the microvasculature. Changes in the internal organs are characterized by a serous-hemorrhagic lymphadenitis, abomasitis, enteritis, colitis and pattern associated with the deposition of immune complexes - serous glomerulonephritis. There are phenomena of hyperemia of stasis, degenerative and necrotic processes with bacterial emboli in the lumen of blood vessels in the parenchymatous organs. Changes in the spleen are identified as septic spleen. Organs of the immune system are characterized by the decrease of level of structural components and the complete absence of germinal centers. The decrease of level of important structural components (lymphocytes) in the organs of immunogenesis in calves, the absence of the marked inflammatory reaction indicate a worsening of immunosuppression in the development of septic process and the failure of protective mechanisms against the expansion of opportunistic microorganisms. The changes described are characteristic for sepsis with development of multiple organ failure caused by autointoxication and damages of parenchymatous organs. Results obtained reveal the involvement of rhodococci in the group of opportunistic microorganisms in the development of sepsis as terminal stage of infectious process at infections caused by opportunistic microorganisms. The constant persistence of rhodococci in the composition of the microbiocenosis of the biotopes of the bovine gastrointestinal tract determines the high risk of their involvement in the development of infectious pathology that must be considered in the development of anti-epizootic measures.